Content-specific interpretation biases in clinically anxious children. (October 2019) - Klein, Anke M.; Rapee, Ronald M.; Hudson, Jennifer L.; Morris, Talia M.; Schneider, Sophie C.; Schniering, Carolyn A.; Becker, Eni S.; Rinck, Mike
Abstract: Cognitive theories of anxiety suggest that anxious children interpret negatively only those materials specifically related to the content of their anxiety. So far, there are only a few studies available that report on this postulated content-specificity of interpretation processes across different anxiety disorders in children, and most of them focused on social anxiety. Therefore, we examined interpretation bias and its content-specificity in a group of clinically anxious children between the ages of 6–12 years with various anxiety disorders, using an "ambiguous scenarios" task. Children were asked to finish scenarios that were related to either social threat, general threat, or separation threat. In total, 105 clinically anxious children, 21 control children and their mothers were assessed with the ADIS-C/P and the Spence Children's Anxiety Scale. As expected, clinically anxious children provided significantly more negative endings to the scenarios than control children. Within the clinically anxious group, specific interpretation biases were found: Interpretation of scenarios related to social threat, general threat, and separation threat were only predicted by the children's self-reported levels of social anxiety, generalized anxiety, and separation anxiety, respectively. These findings support the content-specificity hypothesis that clinically anxious children display interpretation biases that are specific to fear-relevant stimuli. Highlights: Anxious children provided more negative endings to ambiguous scenarios than non-anxious peers. Anxious children display interpretation biases that are specific to fear-relevant stimuli. Interpretation related to social threat was only predicted by social anxiety. Interpretation related to general threat was only predicted by generalized anxiety. Interpretation related to separation threat was only predicted by separation anxiety.